The Role of Recruitment and Selection in Achieving Superior HR Performance in the Industrial Sector - Hesti Widianti; Arifia Yasmin; Hikmatul Maulidah; Bahri Kamal; Ririh Sri Harjanti (Ilomata International Journal of Management, 2026)
This study examines the association between recruitment, selection, and human resource (HR) performance in Indonesia's industrial sector a context underrepresented in existing HR literature despite its distinct labor market characteristics, including a rapidly formalizing HR infrastructure and sector-specific skill demands in manufacturing, automotive, and textile industries. While prior studies confirm positive relationships between talent acquisition practices and employee performance, evidence from emerging economy industrial firms operating under semi-formalized HR systems remains limited, and the combined predictive role of recruitment and selection has rarely been tested within this context. Using a cross-sectional survey of 200 employees from industrial companies in Central Java and multiple linear regression analysis, this study finds that recruitment (β = 0.456, p < 0.001) and selection (β = 0.523, p < 0.001) are each positively associated with HR performance, together accounting for 67.8% of its variance (R² = 0.678). Because the design is cross-sectional, these results indicate association rather than causation. The findings suggest that more systematic and structured talent acquisition practices correspond with better employee performance outcomes, and offer sector-specific empirical evidence to inform HR policy in Indonesian industrial firms where formal recruitment and selection standards are still developing.